2017
DOI: 10.1021/acs.joc.7b01006
|View full text |Cite|
|
Sign up to set email alerts
|

Regioselective Synthesis, NMR, and Crystallographic Analysis of N1-Substituted Pyrazoles

Abstract: A systematic study of the N-substitution reactions of 3-substituted pyrazoles under basic conditions has been undertaken. Regioselective N1-alkylation, -arylation, and -heteroarylation of 3-substituted pyrazoles have been achieved using KCO-DMSO. The regioselectivity is justified by the DFT calculations at the B3LYP/6-31G**(d) level. A consistent steric effect on chemical shift has been observed for N-alkyl pyrazole analogues. Twenty-five X-ray crystallographic structures have been obtained to confirm the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Several experimental techniques have been explored to study the proton transfer in pyrazoles and their derivatives, including mass spectrometry, IR spectroscopy and NMR spectroscopy [38,39,[80][81][82][83][84] NMR is one of the most frequently used techniques for identification of chemical compounds and is also used to investigate chemical processes, for instance through kinetic studies. In the present context we will focus mainly on the use of NMR spectroscopy for studies related to tautomerism [39].…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental techniques have been explored to study the proton transfer in pyrazoles and their derivatives, including mass spectrometry, IR spectroscopy and NMR spectroscopy [38,39,[80][81][82][83][84] NMR is one of the most frequently used techniques for identification of chemical compounds and is also used to investigate chemical processes, for instance through kinetic studies. In the present context we will focus mainly on the use of NMR spectroscopy for studies related to tautomerism [39].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…It was previously stated that, in the presence of two annular nitrogen atoms with pyrrole and pyridine-like characters, the one participating in nucleophilic substitution is the basic pyridine-like nitrogen [6]. However, it was later shown by Huang et al that regioselective synthesis of N1 substituted pyrazoles could be achieved under specific conditions, which led them to investigate the electron density on the ring-nitrogen theoretically through density functional theory (DFT) calculations at the B3LYP/6-31G**(d) level, having concluded that the major negative charge was concentrated on the pyrrole-like nitrogen [83]. Nevertheless, organic synthesis based on pyrazole synthons should regard carefully two main aspects that strongly influence the reactivity of the molecule, the medium or environment in which reactions occur and the substitution pattern on the ring system.…”
Section: Pyrazoles In Organic Synthesismentioning
confidence: 99%
“…Therefore, despite the limitations associated with the [3+2]‐dipolar cycloadditions at both the sulfoxide and sulfone levels, C(4) substituted sulfoxide and sulfone pyrazole derivatives can be accessed readily in synthetically useful quantities in the same overall number of synthetic steps. Regioselective N ‐alkylation using alkyl bromides and K 2 CO 3 in DMSO afforded the alkylated products in high combined yields, with the 5‐carboxylate formed preferentially in all instances, consistent with selective alkylation of the major tautomer present in DMSO (Scheme ). Hydrolysis of the ester moiety to the carboxylic acid 20 and subsequent amide coupling gave pyrazole 21 illustrating that the use of α ‐diazoacetates as dipoles and α ‐sulfenyl‐ β ‐chloroacrylamides as dipolarophiles allows access not only to the generation of highly functionalised pyrazoles but importantly functionalised pyrazoles amenable to significant further synthetic transformations.…”
Section: Resultsmentioning
confidence: 58%
“…There are several reports which provide diverse synthetic protocols to synthesize N-substituted pyrazolines and/or triazole derivatives, which suffer from several short comings such as prolonged reaction time, multistep protocols, use of hazardous solvents, and expensive catalysts [31][32][33][34][35][36]. In view of this, we herein report our investigation toward the development of multicomponent reaction by mechanochemical solvent-free approach which overcome most of the demerits of conventional methodology.…”
Section: Introductionmentioning
confidence: 99%